The Influence of Employee-Perceived High-Commitment Work System on Employee Innovation Behavior in China - Chen, Sidi; Wang, Jia-Fure (The Journal of Behavioral Science, 2024)
For organizations, enhancing employee innovation behavior (EIB) is among the most effective means to gain competitive advantage in the current modern business environment. Based on the conservation of resources theory, this study proposed a model to investigate the influence of the employee-perceived high-commitment work system (EPHCWS) on EIB, with two intervening variables, job embeddedness (JE) as the mediating variable, and creative self-efficacy (CSE) as the moderating variable. In total, 601 valid questionnaires were collected from Chinese employees between November to December 2022. Structural equation modeling technique was used to test the hypotheses. Results showed that EPHCWS positively affected EIB (β = 0.36, p < .001, t = 11.93) and JE (β = 0.26, p < .001, t = 7.86). When JE mediated the relationship between EPHCWS and EIB, the direct effect was significant (β = 0.28, p < .001, t = 9.30). Furthermore, JE positively affected EIB (β = 0.33, p < .001, t = 9.31), indicating that it exerts a partial mediation effect on the relationship between EPHCWS and EIB. Additional moderation results revealed that the interaction between EPHCWS and CSE significantly affected EIB (β = 0.08, p < .01, t = 3.27), which indicated that CSE moderated the effect of EPHCWS on EIB. The study suggests that managers should increase employees’ positive perceptions of the organization-implemented high-commitment work system and enhance EIB by promoting JE and CSE.